2020
DOI: 10.1002/app.49948
|View full text |Cite
|
Sign up to set email alerts
|

Impact of renewable carbon on the properties of composites made by using three types of polymers having different polarity

Abstract: Pine wood derived biocarbon (BioC) is investigated as a renewable alternative to carbon black (CB) for plastics and composites applications. Three different polymers with different polarity were used to prepare the composites: polypropylene (PP), polylactic acid (PLA), and polyamide 6 (PA6). Comparatively, CB had a nodule size of $300 nm and surface area of 8 m 2 /g, whereas BioC showed an average particle size of $950 nm and surface area of $260 m 2 /g, respectively. CB, in the composites, was found in large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Contrary to MMT, the surface of BC particles was not modified, which in this case indicates the necessity to use surface modification. Previous studies confirmed the presence of structure self-compatibility for composite systems containing the BC-based fillers [ 23 , 33 , 34 , 35 ]. However, the polarity of the PLA chains is too low to form strong bonds with functional groups on the surface of BC.…”
Section: Resultsmentioning
confidence: 58%
“…Contrary to MMT, the surface of BC particles was not modified, which in this case indicates the necessity to use surface modification. Previous studies confirmed the presence of structure self-compatibility for composite systems containing the BC-based fillers [ 23 , 33 , 34 , 35 ]. However, the polarity of the PLA chains is too low to form strong bonds with functional groups on the surface of BC.…”
Section: Resultsmentioning
confidence: 58%
“…However, the previously reported results are suggesting some additional features like self-compatibility of the blend after EBA addition [22]. That phenomenon was already confirmed for many other types of thermoplastic blends, since the addition of polyester component is leading to the formation of copolymers, especially when the reactive component of the modifier is forming the chemical bond with the PLA hydroxyl end groups [16,27,28]. Interestingly, for the prepared blends the self-compatibilization of the unmodified POM-PLA blend was confirmed, since the matrix structure was characterized by smooth surface and lack of visible phase separation.…”
Section: Structure Evaluation -Scanning Electron Microscopy Observationsmentioning
confidence: 55%
“…11 The benefits of using nylon 6 are its remarkable mechanical properties, including rigidity and hardness, the ability to perform under elevated temperatures and pressures, and resistance to corrosion and abrasion. [11][12][13] Various fillers are typically incorporated into the nylon matrix to boost various properties and extend applications. Commonly used reinforcing materials and fillers such as carbon fibers, nanotubes, and graphene; used in engineering plastics for manufacturing automotive composites, are high-density, expensive, and not sustainable materials.…”
Section: Introductionmentioning
confidence: 99%